A MPCC approach on a Stackelberg game in an electric power market : changing the leadership - Rodrigues, Helena Sofia (2008)
An electric power market is studied as a Stackelberg game where two firms, A and B, produce energy. It is analyzed two distinct situations, according to the firm who plays the leader role: the first one, when the firm A is the leader and the other firm is the follower, and the second that is the reverse of the players roles. The main goal is to understand the behavior of the various agents that compose the electric power network, such as transmissions capacity, quantities of power generated and demanded, when changing leadership. The problem is formulated as a Mathematical Program with Complementarity Constraints (MPCC) and reformulated into a Nonlinear Program (NLP), allowing the use of robust NLP solvers. Numerical results are presented and some final considerations are carried out.